Role of Inflammatory Markers as a Risk Factor for Community-Acquired Pneumonia Management - Ruta Nutautiene; Irmantas Aleksa; Ieva Janulaityte; Erika Skrodeniene; Kristina Bieksiene; Diana Zaliaduonyte; Darius Batulevicius; Astra Vitkauskiene (Medicina)
Background and Objectives: Community-acquired pneumonia (CAP) remains a major health burden worldwide, with high morbidity and mortality, particularly among older adults and those with comorbidities. This study aimed to evaluate the etiological factors of CAP and to investigate systemic inflammatory markers (IL-6, IL-8, IFN-γ, and G-CSF) in blood samples collected from CAP patients to identify which markers could be targets for potential etiological, clinical, and therapeutic interventions. Materials and Methods: A prospective study was conducted in 41 patients with confirmed CAP hospitalised during the winter season of 2024–2025. Clinical, demographic, and laboratory data were collected at admission and seven days later. Serum IL-6, IL-8, IFN-γ, and G-CSF concentrations were measured using a multiplex assay. Results: Aetiology was identified in 87.8% of cases, with typical bacterial pathogens being more prevalent among older, smoking patients, while atypical pathogens were more common among younger, non-smoking patients. Hospitalisation and increased inflammatory markers were associated with older age. After seven days of treatment, significant decreases in IL-6, IFN-γ, and G-CSF concentrations were observed. IFN-γ levels were significantly higher in patients with atypical aetiology. Higher concentrations of IL-8 and G-CSF were associated with hospitalisation. IL-6 levels were positively correlated with age, C-reactive protein (CRP), and pneumonia severity index (PSI) scores. Conclusions: Systemic inflammatory markers, especially IL-6, IL-8, IFN-γ, and G-CSF, may be valuable tools in managing generalised pneumonia. They can help to differentiate etiologically, assess disease severity, and make treatment decisions.